A Game of Whac-A-Mole: The BDS Movement and Its Fluidity across International Political Opportunity Structures. Issue 3 (1st December 2022) - Lutz, Naama
Abstract: This article focuses on the Boycott, Divestment, and Sanctions (BDS) movement's utilization of 'fluidity, ' conceptualized as the ability to adapt campaign tactics to multiple arenas and political opportunity structures simultaneously. Framing BDS as both a social movement and a transnational advocacy network, it demonstrates the movement's fluidity in the context of three campaigns: the campaign at the 65th FIFA (Federation Internationale de Football Association) congress in 2015, which illustrates an 'outsider' strategy aimed at intergovernmental institutions; the 2014 Olive Declaration of municipalities endorsing BDS, which illustrates how local 'insider' campaigns can combine to create a translocal campaign; and the 'Ferguson-Gaza moment' in 2014, which illustrates how movements can engage at the level of civil society and embed themselves in the broader global justice movement.